Model Pembelajaran Holistic Pada Mata Pelajaran Pendidikan Agama Islam Di SMA Islamic International Boarding School Al-Izzah Batu - Nurul Novitasari (LPPM Institut Agama Islam Al-Hikmah Tuban, 2018)
Abstract, the success of the learning process can’t be separated from the ability of teachers to develop learning models oriented to build effective intensity of student involvement in the learning process. Therefore, it is necessary to have a method or approach to learning. In this case, one approach to learning t is Holistic. This holistic have been applied in al-Izzah high school Batu, this school has a learning model that is comprehensive (holistic) and train the learners more active to improve the diversity of learners through Islamic education in shaping meta-cognition that lead learners achieve learning objectives. To prove this, it is necessary to study further the research study, for which researchers interested in conducting research on the holistic learning model in the subject of PAI. In this study, there are three objectives are: 1) Assess the holistic approach to learning on the PAI subjects in SMA al-Izzah Batu. 2) Assess the holistic learning strategies on PAI subjects in SMA al-Izzah Batu. 3) Assess the holistic learning method on PAI subjects in SMA al-Izzah Batu. 4) Assess evaluation in holistic learning on PAI subjects in SMA al-Izzah Batu. This research is qualitative research, case study method. al-Izzah senior high school selected as the research object because it has implemented Holistic as a model, especially in PAI learning, learning combines Islamic spiritual and intellectual development of students. Data obtained by interview), observations and documents. Data analysis using data reduction, data display and drawing conclusions or verification. There are four results are: (1) a holistic approach to learning on PAI subjects in SMA al-Izzah leads student in centered teaching; (2) a holistic learning strategies on PAI subjects in SMA al-Izzah lead to active learning; (3) holistic learning method on PAI subjects in SMA al-Izzah used the lecture method, discussion, question and answer, assignment and others; and (4) evaluation of learning in high school holistic al-Izzah based daily tests, repeat monthly, midterms, final exams, student behavior in schools, dormitories and houses.